Surgical resection of pulmonary inflammatory pseudotumors: long-term outcome. (July 2017) - Peretti, Marine; Radu, Dana M; Pfeuty, Karel; Dujon, Antoine; Riquet, Marc; Martinod, Emmanuel
Background: Pulmonary inflammatory pseudotumors are rare lesions that remain problematic in several aspects, especially regarding the therapeutic strategy. The goal of this study was to evaluate long-term survival in a multicenter series of patients who required surgery for pulmonary inflammatory pseudotumors. Methods: Thirty-six cases of pulmonary inflammatory pseudotumors, operated on in 3 French thoracic surgery departments between 1989 and 2015, were studied retrospectively. We recorded pre-, peri- and postoperative data for each patient, and long-term survival was analyzed. Results: There were 22 men and 14 women. Mean age was 53.5 years (range 14–81 years). Three pneumonectomies, 1 bilobectomy, 19 lobectomies, 2 segmentectomies, 10 wedge resections, and 1 biopsy were performed. Complete resection was carried out in 32 (88.8%) patients. Median follow-up was 76 months. Five-year and 10-year survival rates were respectively 86.8% and 81.7% (96% and 90% for patients with R0 resection). Conclusions: Long-term survival was excellent for patients with pulmonary inflammatory pseudotumors who benefited from surgery, especially when surgical resection was complete. These results confirm that surgical resection must be proposed as the first-line treatment for patients with pulmonary inflammatory pseudotumors.